Matrix microstructure evolution during the fabrication of SiCf/Ti60 composites - Zhicong Gan; Yumin Wang; Xu Zhang; Lina Yang; Qiuyue Jia; Xu Kong; Guoxing Zhang; Qing Yang; Rui Yang (Journal of Materials Research and Technology, 2024)
Microstructure evolution during the hot isostatic pressing (HIP) of continuous silicon carbide fiber-reinforced Ti (SiCf/Ti) composites has not been investigated. In this study, SiCf/Ti60 composites were prepared via the HIP solidification method of Ti60 precursor wires. The evolution of the microstructure of the Ti60 precursor wires and SiCf/Ti60 composites was characterized using electron backscatter diffraction microscopy and transmission electron microscopy techniques. The results showed that the deformation of α-Ti was mainly accomplished by basal dislocations and prismatic dislocations slip during the HIP process. After the completion of HIP, the low-angle grain boundaries (LAGBs) were reduced to 24.6%, and the average grain size of α-Ti was increased to 7.47 μm2. Two fiber textures, <0001>//axial direction (AD) and <10-10>//AD strength, were present in α-Ti, with a 38% increase in <10-10>//AD strength. The phase contents of 1.0% β-Ti and 0.6% (Ti, Zr)6Si3 precipitated from different locations in the Ti60 matrix and induced changes in misorientation.